Some experiences in the development of agricultural engineering education in Malaysia - Abang Ali, Abang Abdullah (1984)
Agricultural engineering as a profession was first introduced in Malaysia in 1975 with the establishment of the Faculty of Agricultural Engineering at Universiti Pertanian Malaysia. The first batch of agricultural engineering degree students graduated in 1979. In 1983 the faculty produced its first batch of graduates with the Diploma in Agricultural Engineering. There is now interest in postgraduate training with the starting of the M.S. and Ph.D degree programmes in 1982. The government is presently studying the possibility of offering agricultural engineering education at the technician level in Malaysian polytechnics.